2014
DOI: 10.1186/1471-2229-14-121
|View full text |Cite
|
Sign up to set email alerts
|

VMP1-deficient Chlamydomonas exhibits severely aberrant cell morphology and disrupted cytokinesis

Abstract: BackgroundThe versatile Vacuole Membrane Protein 1 (VMP1) has been previously investigated in six species. It has been shown to be essential in macroautophagy, where it takes part in autophagy initiation. In addition, VMP1 has been implicated in organellar biogenesis; endo-, exo- and phagocytosis, and protein secretion; apoptosis; and cell adhesion. These roles underly its proven involvement in pancreatitis, diabetes and cancer in humans.ResultsIn this study we analyzed a VMP1 homologue from the green alga Chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…Our studies may now explain the apparently disparate phenotypes observed in different organelles such as mitochondria and chloroplasts in Chlamydomonas [26]; ER, Golgi and contractile vacuole in Dictyostelium [18], and processes as diverse as cytokinesis, secretion and endocytosis [18, 20, 26, 39, 40]. All these organelles and processes can potentially be affected by altered MCS as these contacts regulate the traffic of lipids, Ca2+ and signaling molecules [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our studies may now explain the apparently disparate phenotypes observed in different organelles such as mitochondria and chloroplasts in Chlamydomonas [26]; ER, Golgi and contractile vacuole in Dictyostelium [18], and processes as diverse as cytokinesis, secretion and endocytosis [18, 20, 26, 39, 40]. All these organelles and processes can potentially be affected by altered MCS as these contacts regulate the traffic of lipids, Ca2+ and signaling molecules [1].…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of VMP1 in model organisms causes pleiotropic phenotypes, leading to the hypothesis that VMP1 may play additional non-autophagic roles. Studies in Dictyostelium [18], plants [20] and Chlamydomonas [26] suggest that VMP1 is involved in processes as diverse as protein secretion, endo- and phagocytosis, osmoregulation, cytokinesis, regulation of organelle's function and morphology. How a single protein can regulate such a wide range of processes is not known.…”
Section: Introductionmentioning
confidence: 99%
“…cerevisiae Vtc1p is present in a complex that is involved in acidocalcisome membrane fusion events and polyphosphate synthesis (Ogawa et al, 2000;Uttenweiler et al, 2007;Hothorn et al, 2009), while S. cerevisiae Vtc4p is a polyphosphate polymerase (Hothorn et al, 2009). Other proteins associated with various vacuole types have been analyzed through mutational studies and shown to be involved in contractile vacuole function, autophagy, cytokinesis, and lysosomal inactivation of Parainfluenza virus (Komsic-Buchmann et al, 2012;Ding et al, 2014;Tenenboim et al, 2014). The Vtc proteins of S. cerevisiae appear to assemble into a complex whose formation requires all of the polypeptide subunits of the complex.…”
Section: Structure and Function Of Vtc1mentioning
confidence: 99%
“…To determine whether this morphological change in starch grains correlated with an increase in starch content in the PAM amiRNA cells, we measured starch levels enzymatically and found no significant difference between the knockdown and control cells. Enlarged starch grains without a concomitant increase in starch levels were previously noted in vacuolar membrane protein-1 (VMP1) knockdown strains, which also displayed abnormal Golgi morphology (Tenenboim et al, 2014). These results suggest an impact of PAM knockdown on Golgi function.
10.7554/eLife.25728.023Figure 10.Golgi function is selectively compromised in C. reinhardtii PAM knockdown cells.( A ) Transmission electron micrographs showing enlarged starch grains in a representative PAM amiRNA cell compared to a control cell.
…”
Section: Resultsmentioning
confidence: 71%